Assessment of Quality of Life and Prevalence of Depression Among Type 1 Diabetic Patients at Prince Mansour Military Hospital, Taif, KSA - Al-Nozha, Sultan; AlShehri, Khalid; AlJabri, Manal; Abozaid, Hani; Atalla, Ayman (International Journal of Innovative Research in Medical Science, 2024)
Background: Patients with diabetes were shown to report poor quality of life and significant depressive symptoms. Only a dearth of surveys was conducted to evaluate the extent of depression among Saudi patients with diabetes and how depression mediate the effect of diabetes on perceived quality of life. Method: The study is a cross sectional questionnaire-based observational investigation using a simple random sampling scheme. We utilized World Health Organization Quality of Life Brief Version (WHOQOL-BREF) and Primary Health Questionnaire PHQ-9 to evaluate depressive symptoms and quality of life. We used generalized linear regression and mediation analysis to estimate the effect of clinical and demographic variables on quality of life and the mediating effect for depressive symptoms. Results: (n = 203) agreed to be included in the study. The prevalence for severe depression was (11.3%), and for moderate depression was (18.7%) among the participating patients. Poor QoL was found in retired patients, prolonged duration of diabetes, depressive score, and experiencing DKA. Notably, we found significant interaction between duration of DM and HbA1c level in terms of their combined effect on quality of life. Among patients with prolonged diabetes duration HbA1c level was associated with poorer quality of life. However, paradoxically, among newly diagnosed diabetes patients the higher the HbA1c the better was the quality of life. Age effect was negative on the QoL, after adjusting for the HbA1c*DM duration interaction. We found that depression score significantly mediated the negative effect of age on quality of life among patients living with diabetes (Sobel test t = -2.851, p = 0.004); however, the depression-mediated effect on the path from duration of diabetes to quality-of-life score was statistically not significant (Sobel test t = -0.021, p = 0.984). Recommendations: Patients with diabetes should be screened and treated for symptoms of depression throughout the course of their illness, given their detrimental effect on their life quality. Older patients with diabetes require amelioration of depressive symptoms given their effect on life quality regardless of duration of diabetes or presence of complications.